The effects of single nucleotide polymorphisms in glutamatergic neurotransmission genes on neural response to alcohol cues and craving - Bach, Patrick; Mann, Karl; Rietschel, Marcella; Kiefer, Falk; Vollstädt-Klein, Sabine (Addiction biology, 2015)
The aim of the current study was to determine genotype effects of four single nucleotide polymorphisms (SNPs) in the genes of the N-Methyl-d-aspartate receptor (GRIN1, GRIN2A, GRIN2C) and kainate receptor (GRIK1), which have been previously associated with alcoholism, on behavior, neural cue-reactivity and drinking outcome. Eighty-six abstinent alcohol dependent patients were recruited from an in-patient setting. Neuropsychological tests, genotyping and functional magnetic resonance imaging (fMRI) were used to study genotype effects. GRIN2C risk allele carriers displayed increased alcohol cue-induced activation in the anterior cingulate cortex (ACC) and dorsolateral prefrontal cortex (dlPFC). Neural activation in the ACC positively correlated with craving for alcohol (r = 0.201, P = 0.032), whereas activation in the dlPFC showed a negative association (r = −0.215, P = 0.023). In addition, dlPFC activation predicted time to first relapse (HR = 2.701, 95%CI 1.244-5.864, P = 0.012). GRIK1 risk allele carriers showed increased cue-induced activation in the medial prefrontal (PFC) and orbitofrontal cortex (OFC) and in the lateral PFC and OFC. Activation in both clusters positively correlated with alcohol craving (rmedOFC, medPFC = 0.403, P = 0.001, rlatOFC, latPFC = 0.282, P = 0.008), and activation in the cluster that encompassed the medial OFC predicted time to first relapse (HR = 1.911, 95%CI 1.030-3.545, P = 0.040). Findings indicate that SNPs in the GRIN2C and GRIK1 genes are associated with altered cue-induced brain activation that is related to craving for alcohol and relapse risk.